STRATEGI PEMASARAN INDUSTRI BATU BATA MERAH DALAM MENINGKATKAN EKONOMI KELUARGA PERSPEKTIF EKONOMI ISLAM - masyhuri masyhuri; nur syarinah (AL-KHARAJ, 2022)
This article discusses the marketing strategy of the red brick industry in improving the family economy from an Islamic economic perspective (study on the Bukaka red brick business, Bone Regency). The red brick business today does have opportunities that have been reduced due to the presence of light bricks, the quality and quantity of the product is not met and the marketing strategy is mediocre. This study aims to find out how the concept of the marketing strategy of the red brick industry in improving the family economy in the Bukaka red brick business of Bone Regency and how Islamic economic views regarding the marketing strategy of the red brick industry in improving the family economy in the Bukaka red brick business of Bone Regency.Based on the research objectives above, the type of research used is field research (Field Research) with qualitative methods that describe a complete picture of something being researched. The researcher collected data from the field according to the problems related to this article. Data collection techniques used are observation, interviews and documentation.The results of this study indicate that the marketing strategy carried out by the Bukaka red brick business in Bone Regency is to apply the Marketing Mix principle or marketing mix that does not conflict with Islamic values. And also follow the marketing practices of the Prophet Muhammad SAW. In accordance with the nature of the Prophet Muhammad, namely: Siddiq, Amanah, Tabligh, Fathanah. With these values, the Bukaka red brick business in Bone Regency is able to continue to exist and thrive in the midst of competitive competition.